2007
DOI: 10.1021/es062402y
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Dioxin-like PCBs in Fish:  An Application for Risk Assessment

Abstract: It is widely accepted that a congener-specific analysis of polychlorinated biphenyls (PCBs), rather than traditional Aroclor equivalent total PCB analysis, is required for risk assessment. This is based on the fact that environmental processes alter the original distribution of PCB congeners in Aroclors and that toxicity varies considerably among the congeners with dioxin-like PCBs (dl-PCBs) generally being among the most toxic. Using the largest known dl-PCB fish dataset, here we present a likely composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
46
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 26 publications
12
46
0
Order By: Relevance
“…Results from a study by Bhavsar et al (2007) about the distribution of the DL-PCB congeners (absolute concentrations) in different fish species from 1700 locations in Ontario's inland lakes/rivers and the Great Lakes (Canada) are similar as our results. They reported the two MO-PCBs 118 and 105 as the most abundant DL-PCB congeners while the most toxic DL-PCB congeners, PCBs 126 and 169 contributed on average only 0.027% and 0.004% of total-PCBs, respectively (Bhavsar et al, 2007). Bhavsar et al (2007) also reported that all NO-PCBs (i.e.…”
Section: Mchugh Et Al (2010) Reported Concentrations In Irish Eel Wsupporting
confidence: 85%
See 3 more Smart Citations
“…Results from a study by Bhavsar et al (2007) about the distribution of the DL-PCB congeners (absolute concentrations) in different fish species from 1700 locations in Ontario's inland lakes/rivers and the Great Lakes (Canada) are similar as our results. They reported the two MO-PCBs 118 and 105 as the most abundant DL-PCB congeners while the most toxic DL-PCB congeners, PCBs 126 and 169 contributed on average only 0.027% and 0.004% of total-PCBs, respectively (Bhavsar et al, 2007). Bhavsar et al (2007) also reported that all NO-PCBs (i.e.…”
Section: Mchugh Et Al (2010) Reported Concentrations In Irish Eel Wsupporting
confidence: 85%
“…PCB 77, PCB 81, PCB 126, and PCB 169) are the lowest DL-PCB contributors to total-PCBs levels in fish. Also following Bhavsar et al (2007), the abundance of DL-PCBs in fish is generally in the order of In our study the 1,2,3,7,8-PentaCDD and the 2,3,4,7,8-PentaCDF congeners accounted for 35% and 38% respectively of the total PCDD/ Fs congeners (expressed as pg WHO 1998 TEQ g − 1 (lower bound) on fresh weight basis; Fig. 3A).…”
Section: Mchugh Et Al (2010) Reported Concentrations In Irish Eel Wsupporting
confidence: 61%
See 2 more Smart Citations
“…set a threshold of 8 pg·g −1 wet weight (ww) for the toxic equivalent concentration (TEQ) standardised to the 2378 tetrachlorodibenzodioxin toxicity in all fish species, except eel, for which the threshold was set at 12 pg·g −1 ww. Most of the TEQ load in fish is due to dioxin-like PCBs (DL-PCBs), and is correlated with the total PCB load (Bhavsar et al, 2007a;Bhavsar et al, 2007b) or the sum of indicator congeners (ΣiPCB; Babut et al, 2009). Thus a ΣiPCB load of 154 ng.g −1 (ww, confidence interval 120−200 ng.g −1 ww) generally corresponds to an exceedance of the TEQ regulatory limit.…”
Section: Introductionmentioning
confidence: 99%